Implementation of a clinical decision support system improves compliance with restrictive transfusion policies in hematology patients. Issue 8 (23rd April 2015) - Butler, Caroline E.; Noel, Simon; Hibbs, Stephen P.; Miles, David; Staves, Julie; Mohaghegh, Payam; Altmann, Paul; Curnow, Elinor; Murphy, Michael F.
<x xml:space="preserve">Abstract</x> BACKGROUND There is increasing evidence for restrictive red blood cell (RBC) transfusion but compliance with recommended transfusion triggers is variable. A clinical decision support system (CDSS) has been found to reduce unnecessary transfusion in some clinical settings when physicians are advised they are noncompliant with the current guidelines. The objective was to assess the impact of a CDSS for blood product ordering in patients with hematologic disease. STUDY DESIGN AND METHODS All platelet (PLT) and RBC transfusions were identified in hematology patients in three periods: before (baseline), immediately after (CDSS1), and 7 months after implementation of CDSS for blood ordering (CDSS2). Compliance with the recommended transfusion triggers was monitored for all orders made by CDSS or non‐CDSS methods during each period. RESULTS Ninety‐seven patients with a variety of hematologic diagnoses received 502 RBC and 572 PLT transfusions during the three periods with no significant difference in 1) the mean number of transfusions per patient, 2) the proportion of patients transfused, 3) posttransfusion hemoglobin (Hb), and 4) pre‐ and posttransfusion PLT count, although mean pretransfusion Hb decreased. The proportion of noncompliant RBC and PLT transfusion requests improved from baseline to CDSS2 (69.0% to 43.4% p ≤ 0.005 for RBCs; and 41.9% to 31.2%, p = 0.16 for PLT) when all orders were compared, although this improvement was not significant at the 5% level for PLTs. CONCLUSIONS The introduction of CDSS for blood product ordering supported by education and physician feedback in the hematology setting had an immediate impact on improving compliance with guidelines for restrictive transfusion practice.